Human Existence as Caliph and Implementation of Islamic Education - Darwis Hude; Made Saihu (RIRAI Publisher, 2024)
This article aims to examine more deeply the essence of humanity in Islamic education. In its study, this paper uses the literature study method, namely studying human essence from primary sources of the Islamic religion such as the Al-Qur'an and the Hadith of the Prophet. Education that ignores the goals, functions, and tasks of human creation from the concept of Islamic education is a concrete form of distance from Islamic educational practices. This article concludes that human existence is a combination of physical elements and spiritual elements or between material elements and immaterial elements, the elements of body, mind and spirit are a unity that cannot be separated. Since the time of creation, humans have been equipped by God with the potential to be